Use and awareness of herbal medicines among literate population - PRAMOD KUMAR MAHISH; RAJU MAHOBIA; JITENDRA YADAV (International Journal of Pharma and Bio Sciences, 2016)
Herbal medicines are used to cure diseases since a great many year back in light of its simple accessibility, social worthiness and less side effect. As of late a fast request of herbal products is seen in the worldwide situation on account of unfavorable impact of advanced medicines. A survey based study was composed thusly to perceive the awareness about herbal medicines among literate populace. Most extreme people groups (69.67%) satisfy with the use of herbal products. Maximum individuals fall in awareness index 4 and 3 (39.13 and 28.26%) it signifies awareness of people with herbal products. The general population use herbal medication for the most part for cosmetics took after by teeth consideration and assimilation. Awareness index was found more in rural population and peoples with higher education level. Now it is concluded peoples have acceptable information about herbal medicines, philosophy of usage and manufacturer.